Проблеми інтеграції відновлювальних джерел електроенергії в "слабкі" електричні мережі - Кириленко, О.В.; Павловський, В.В.; Лук'яненко, Л.М.; Трач, І.В. (Технічна електродинаміка, 2012)
The features of the connection of power plants constructed using renewable sources of energy to electrical networks and their impact on the operating conditions of such networks are considered. The key point that should be considered when selecting the location of such stations are identified.